Broca's area and its striatal and thalamic connections: a diffusion-MRI tractography study - Ford, Anastasia; Triplett, William; Sudhyadhom, Atchar; Gullett, Joseph M.; McGregor, Keith; FitzGerald, David; Mareci, Thomas; White, Keith; Crosson, Bruce (Frontiers in Neuroanatomy, 2013)
In the recent decades structural connectivity between Broca’s area and the basal ganglia has been postulated in the literature, though no direct evidence of this connectivity has yet been presented. The current study investigates this connectivity using a novel diffusion-weighted imaging (DWI) fiber tracking method in humans in vivo. Our findings suggest direct connections between sub-regions of Broca’s area and the anterior one-third of the putamen as well as the ventral anterior nucleus of the thalamus. Thus, we are the first to provide a detailed account of inferred circuitry involving basal ganglia, thalamus, and Broca’s area, which would be a prerequisite to substantiate their support of language processing.